Penerapan Metode Metode Multi-Attribut Border Approximation Area Comparison (MABAC) dalam Penentuan Akademi Kebidanan (AKBID) Terbaik - Rizki Dermawan; Sinar Sinurat (Journal of Computer System and Informatics (JoSYC), 2021)
The Midwifery Academy (AKBID) is one of the options for continuing post-graduate education, especially in the city of Medan. A quality private midwifery academy greatly influences the course of an education. To easily compete in the world of work. Because a good AKBID has a good accreditation, AKBID accreditation is very influential in the world of work. Especially in the career path, acceptance of new workers. Determining the IMR in the city of Medan is not easy, because there are many IMRs in the city of Medan. There are too many IMRs available, making it difficult to determine the IMR manually, and the election results are sometimes inaccurate and become a problem in determining the best IMR. Decision Support System (DSS) is a system that can assist a person in making accurate and targeted decisions. The method used in the Decision Support System is to use Multi-Attributive Border Approximation Area Comparison (MABAC). This method was chosen because it can assist the decision-making process determining the optimal midwifery academy, in this case the intended alternative is the one who has the right to become the best Midwifery Academy based on the specified criteria.